INSECTICIDAL AND FUNGICIDAL ACTIVITY OF A MAGNESIUM COMPOUND CONTAINING ISOVANILLIC ACID AGAINST LEAF-CUTTING ANT AND ITS SYMBIOTIC FUNGUS - Silva, Eldevan; Marchi, Rafael; Matos, Carla; Silva, Maria; Fernandes, Joao; Bueno, Odair [UNESP]; Carlos, Rose (Soc Brasileira Quimica, 2021)
Pesticides offer a simple, cost-effective solution to ensure food supplies for a growing world population. However, their environmental performance needs improvement if pesticides are to continue contributing importantly. This study explores the insecticidal potential of a magnesium (II) metal complex containing 1,10-phenanthroline and isovanillic acid (MgPhenIso) against leaf-cutting ant (Atta sexdens rubropilosa) and its symbiotic fungus (Leucoagaricus gongylophorus). The MgPhenIso complex is easy-to-prepare, stable in solid state and in aqueous solution, and resistant to sunlight irradiation. The insecticidal activity of MgPhenIso-containing bait against A. sexdens rubropilosa and L. gongylophorus showed a delayed action mode at 2 mg g(-1) (100% kill, 6th day, S-50=2b) and suppressed fungus development and growth. These results, together with earlier investigations on MgPhenIso regarding its absence of toxicity to Zebrafish and Wistar male rats, emphasize the potential of this complex as an environmentally friendly insecticide candidate.
Keywords: pesticide; thermal and light resistance; natural product; agricultural microbiology; Atta sexdens rubropilosa